FORMULASI SEDIAAN MASKER GEL PEEL OFF EKSTRAK DAUN SIRIH CINA (PEPEROMIA PELLUCIDA) - Nasution, Nurul Mawaddah; Br Ginting, Astriani Natalia; Yunus, Muhammad (Jurnal Buana Farma, 2026)
Acne vulgaris is a common skin disorder often associated with increased sebum production and colonization of Cutibacterium acnes on the skin. Peperomia pellucida L. is a medicinal plant known to contain secondary metabolites such as flavonoids, alkaloids, saponins, and tannins, which have potential for use in the development of natural cosmetic formulations. This study aimed to formulate Peperomia pellucida leaf extract into a peel-off gel mask preparation and evaluate its physical characteristics. The extraction of the leaves was carried out using a maceration method with 96% ethanol as the solvent. The obtained extract was then formulated into four different concentrations (0%, 2%, 4%, and 6%) using a gel base consisting of polyvinyl alcohol (PVA), hydroxypropyl methylcellulose (HPMC), triethanolamine (TEA), glycerin, nipagin, nipasol, and distilled water. The evaluation of the formulations included organoleptic observation, homogeneity test, pH measurement, drying time, and spreadability test. The results showed that all formulations produced homogeneous preparations with pH values ranging from 5.75 to 6.20, drying time between 15–25 minutes, and spreadability ranging from 6.3 to 6.8 cm. Increasing extract concentration affected the organoleptic characteristics and drying time of the preparations. Based on the physical evaluation results, the formulation containing 4% extract demonstrated the most optimal physical characteristics compared with the other formulations.